Clinicopathological features and outcome of thyroglobulin elevation and negative iodine scintigraphy (TENIS) patients with negative neck ultrasound: Experience from a thyroid carcinoma clinic in India - Roopa Vijayan; Shanmuga Palaniswamy; Usha Vadayath; Vasantha Nair; Harish Kumar (World Journal of Nuclear Medicine)
Management of differentiated thyroid carcinoma (DTC) patients with thyroglobulin (Tg) elevation and negative iodine scintigraphy (TENIS) and negative neck ultrasound scan causes considerable diagnostic and therapeutic dilemma, especially in resource-poor settings. The aim of this study was to evaluate clinicopathological features and outcome of TENIS patients with negative neck US attending a thyroid cancer clinic in India. From a DTC database of 722 containing 193 TENIS patients, subjects with negative neck US and negative Tg antibody (TgAb) were selected retrospectively and analyzed using appropriate statistical methods. The study group included 64 patients (male – 17, female – 47, mean age – 44.7 ± 12.8 years) with 54 papillary and 10 follicular thyroid carcinomas, American Thyroid Association (ATA) recurrence risk categorization (2009) – low – 16, intermediate – 28, and high – 2 0. Most of the patients became TENIS within 1 year of diagnosis with median Tg level of 6.5 ng/mL (1.2–996 ng/mL) and mean follow-up of 7.8 years. On follow-up, Tg dropped spontaneously in 27 patients, more among the low and intermediate-risk categories. For those with high or increasing Tg level, further imaging (fluorodeoxyglucose positron emission tomography/computed tomography) was done and 14 out of 18 were positive. Treatment included empiric radioactive iodine therapy-16, external beam radiation therapy (EBRT)-7, and lymph node dissection (LND)-10. A favorable outcome was seen in 36 patients and unfavorable in 28. Distant metastases were associated with unfavorable outcome and poor survival. Progression-free survival was significantly better in the Tg group of <10 at the time of TENIS (111 months) compared to the Tg group >10 (72 months). Tg level dropped spontaneously in nearly half the patients, especially if levels were <10 and more so among the low-risk category. Distant metastasis was predictive of unfavorable outcomes. Along with Tg level, the ATA risk category might help to predict clinical course and reduce unnecessary expensive imaging in resource-poor settings.